(untitled) (Journal of Medical Device Technology, 2024)
Heart rate variability (HRV) is a valuable tool for assessing autonomic function and diagnosing cardiovascular diseases. Electrocardiography (ECG) is considered the gold standard for HRV measurements. Photoplethysmography (PPG), a simpler and more convenient method has emerged as an alternative to ECG for HRV measurement. As a result of this technique, many mobile applications have been developed that claim to perform real-time HRV in short periods ranging from 10 seconds to 1 minute. However, HRV requires at least 5-mintues for accurate measurements. Therefore, this study aims to investigate the validity of short-term (5 min) and ultra-short-term (<5 min) HRV measurements obtained through a commercially available smartphone app (Camera Heart Rate Variability app) and compared to a traditional PPG sensor (Shimmer3 GSR+). PPG signals were collected from 16 healthy participants and pre-processed to eliminate noise and reduce motion artifacts. A total of 12 HRV features were then extracted using time-domain analysis (TA) and frequency-domain analysis (FA). Next, HRV features were compared using correlation analysis. TA features using Camera HRV app (meanHR, AVNN, RMSDD, pNN50) showed significant correlation (r > 0.7) at a minimum duration of 0.5-minute, while SDNN required 1 minute. FA features (VLF, LF, LFnu, HFnu) required a minimum duration of 2 minute, while (HF, LF/HF, TP) required 3 minutes. In conclusion, Camera HRV app is suggested to be a valid surrogate to traditional PPG sensors and has the potential to be used in various fields.